2016
DOI: 10.1002/cmdc.201600366
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in Silico, Electrochemical, in Vitro and in Vivo Metabolism of a Homologous Series of (Radio)fluorinated σ1 Receptor Ligands Designed for Positron Emission Tomography

Abstract: The imaging of σ receptors in the brain by fluorinated radiotracers will be used for the validation of σ receptors as drug targets as well as for differential diagnosis of diseases in the central nervous system. The biotransformation of four homologous fluorinated PET tracers 1'-benzyl-3-(ω-fluoromethyl to ω-fluorobutyl)-3H-spiro[2]benzofuran-1,4'-piperidine] ([ F]1-4) was investigated. In silico studies using fast metabolizer (FAME) software, electrochemical oxidations, in vitro studies with rat liver microso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The metabolic stability of rac - 1 , ( S )- 1 , and ( R )- 1 have previously been studied in vitro using RLM in presence of NADPH. After 30 min, rac - 1 showed the lowest stability (∼13%) among the fluoroalkyl homologs tested (Wiese et al, 2016), whereas 73% of intact ( S )- 1 was still present after the same incubation time (Holl et al, 2013). Compared with our results from HLM (14%) this might suggest that ( S )- 1 has higher stability in rats than in human.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The metabolic stability of rac - 1 , ( S )- 1 , and ( R )- 1 have previously been studied in vitro using RLM in presence of NADPH. After 30 min, rac - 1 showed the lowest stability (∼13%) among the fluoroalkyl homologs tested (Wiese et al, 2016), whereas 73% of intact ( S )- 1 was still present after the same incubation time (Holl et al, 2013). Compared with our results from HLM (14%) this might suggest that ( S )- 1 has higher stability in rats than in human.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolism rates have been reported for rac -[ 18 F] 1 or ( S )-[ 18 F] 1 in mice, pigs, and monkeys. In mouse plasma the fraction of unchanged rac -[ 18 F] 1 was 89 ± 3% at 30 min post injection (Wiese et al, 2016). For ( S )-[ 18 F] 1 it was shown that in plasma of piglets 37% of the radioligand remained unchanged at 30 min post injection (Brust et al, 2014a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a subsequent pilot study we performed PET imaging with [ 18 F]fluspidine in orthotopically implanted brain tumors. In general, [ 18 F]fluspidine has been shown to be suitable for brain imaging [ 31 , 33 , 52 ] and thus, we hypothesize that these radioligands are suitable for imaging of Sig1R expressing brain tumors. Preliminary data from these experiments revealed a tumor-to-background SUV ratio (TBR) of >1 for early time points and thus visualization of the tumor in the mouse brain appeared to be feasible.…”
Section: Discussionmentioning
confidence: 99%